2018
DOI: 10.31557/apjcp.2018.19.11.3009
|View full text |Cite
|
Sign up to set email alerts
|

Determining the Survival Rate of Colorectal Cancer in Iran: A Systematic Review and Meta-Analysis

Abstract: Objective:Colorectal cancer is one of the most common causes of death in the world. Despite of remarkable advances in medical sciences, cancer is an important disease and the second cause of death after cardiovascular diseases. The present study was aimed at determining the survival rate of colorectal cancer in Iran.Methods:The present study is a systematic review of national and international electronic databases. Studies that had the inclusion criteria were included in the study, electronically published art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 49 publications
3
15
1
Order By: Relevance
“…On the other hand, the discrepancy could also be due to the difference in participants, in which we assessed patients in the cancer registry whereas the study by Atinafu and his colleagues enrolled patients who were being treated in the clinical setting. Overall rate of survival in our study is also worse than the rate reported from Asian LMICs [26,27,28,29], but better than that of Uganda [30] and Ghana [31], which reported 8.3% and 16.0% 5-year survival respectively. The discrepancy in survival might be mainly due to the variation in the availability of screening facilities and initiation of early treatment.…”
Section: Discussioncontrasting
confidence: 85%
“…On the other hand, the discrepancy could also be due to the difference in participants, in which we assessed patients in the cancer registry whereas the study by Atinafu and his colleagues enrolled patients who were being treated in the clinical setting. Overall rate of survival in our study is also worse than the rate reported from Asian LMICs [26,27,28,29], but better than that of Uganda [30] and Ghana [31], which reported 8.3% and 16.0% 5-year survival respectively. The discrepancy in survival might be mainly due to the variation in the availability of screening facilities and initiation of early treatment.…”
Section: Discussioncontrasting
confidence: 85%
“…(29) Also during a systematic review of 28 studies from different parts of Iran, 12 studies revealed an association between age and CRC prognosis, in that about 12% of these patients were younger than 40 years. (11) However in another group of studies age was not reported as an important prognostic factor. (30,31) It has been elucidated that age at diagnosis has no impact on colorectal cancer specific survival rates, but has an impact on deaths due to other causes and on hazard ratio of age at first diagnosis of colorectal cancer.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, multivariate model analysis revealed a significant improvement in the prognosis of CRC patients during the study period. (9)(10)(11) Since CRC has a high incidence and cancer-related mortality in Iran and East Azerbaijan province, it is necessary to have an epidemiological study of the incidence, sex, age distribution and morphological types of colorectal cancer. The aim of the present study was to determine the most recent epidemiological profile of colorectal cancer along with 1-to 5year colorectal cancer specific survival in East Azerbaijan, Northwest Iran.…”
Section: Introductionmentioning
confidence: 99%
“… 81 , 82 Among other effective factors that can influence the survival rate in patients is smoking and consuming alcohol. 83 Phips and Newcomb in 2011 stated that smoking significantly reduced the survival rate of patients with CRC. 84 To add, the cohort study done by Kangwha cohort study in South Korea stated that the chances of death in CRC patients were about 5 times more than non-alcoholic patients.…”
Section: Discussionmentioning
confidence: 99%